Demystifying Multimodal AI: A Technical Deep Dive - Kiran Chitturi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article explores the transformative impact of multimodal AI systems in bridging diverse data types and processing capabilities. It examines how these systems have revolutionized various domains through their ability to handle multiple modalities simultaneously, from visual-linguistic understanding to complex search operations. The article delves into the technical foundations of multimodal embeddings, analyzes leading models like CLIP and MUM, and investigates their real-world applications across different sectors. Through a detailed examination of current implementations, challenges, and future directions, this article provides insights into how multimodal AI reshapes our interaction with digital information while highlighting its potential and limitations in addressing complex real-world scenarios.